Changes and Clinical Significance of Serum Degraded Monosaccharides in Children with Systemic Lupus Erythematosus - LIN Yi; WANG Zhiliang; ZHAO Haiyan; ZHANG Lijuan; CHANG Hong (Xiehe Yixue Zazhi, 2023)
Objective  To investigate the characteristics of changes in serum degraded monosaccharide levels in children with systemic lupus erythematosus (SLE) and its relationship with the severity of the disease and immune dysfunction.  Methods  Children firstly diagnosed as SLE and hospitalized in the Affiliated Hospital of Qingdao University from January 2019 to March 2022 were enrolled in the SLE group, healthy childrenwho underwent physical examination at the same period were chosen as the control and matched in a ration of 1∶1 in age and sex with the SLE group. The clinical data of both groups were collected. The serum levels of five kinds of degraded monosaccharides, which were mannose, glucosamine, aminogalactose, N-acetyl glucosamine and galactose, were analyzed in both groups. The correlations between serum levels of degraded monosaccharides and SLE disease activity and immunologic markers were analyzed with Pearson correlation coefficient.  Results  Totally 45 children with SLE (13 with mild disease activity, 15 with moderate disease activity, and 17 with severe disease activity) and 50 healthy children were enrolled in the experiment. Compared with the control group, the SLE group showed elevated levels of serum mannose, glucosamine, aminogalactose, N-acetyl glucosamine, and galactose (all P < 0.05); and serum levels of mannose, N-acetyl glucosamine, and galactose gradually increased with increasing disease activity (all P < 0.05). There was no significant difference in glucosamine and aminogalactose levels in children with SLE of different disease activity (all P > 0.05). Pearson correlation coefficient showed that serum degraded monosaccharide levels were positively correlated with disease activity indexes and various immunologic markers.  Conclusions  Serum levels of degraded monosaccharides in children with SLE are elevated and some of which are correlated with disease activity and immune dysfunction.